O pochodzeniu wczesnośredniowiecznych szklanych paciorków z metalową tuleją z wczesnośredniowiecznych ośrodków grodowych w Wielkopolsce i na Ziemi Lubuskiej - Sawicka, Joanna (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2024)
This paper presents a small collection of characteristic early medieval glass beads with a metal sleeve around the duct. They come mainly from the pre-Piast settlement levels of Połupin, Gostchorze, Santok, Kruszwica, Giecz, and Gniezno. The results of the physical and chemical analyses (SEM-EDS and SEM-WDS) have identified the two main types of glass, namely sodium glass of the (Na2O-CaO-Al2O3-SiO2) mineral variety and potassium glass of the CaO-K2O-MgO-Al2O2-SiO2 variety and has allowed a general identification of the sources of raw material for the local Central European workshops producing such beads.